Formação de administradores na PUC-SP: competências do ensino-aprendizagem - Bastos, Fabrício César (2009)
The present study has privileged to check how teachers and students of a graduation course in Business Administration of a private University of São Paulo, have noticed the teaching staff competences. From the survey it was extracted the investigation of the more valuable of the teaching strategies in the teaching staff and students points of view, as well as it has explored the perception of competences development expected to the administrators formation by the students. The aim of the survey was focused on the observation of how the teaching staff uses the competences in the teaching-learning process, and how these have been noticed by the students. Moreover, it was adopted a methodology based on the qualitative survey of exploratory background, choosing an unique case study with the purpose of acquiring more knowledge and enlarging the comprehension of the teaching staff competences theme. By the survey it was possible to draw the answering teachers profile, apart from comparing the points of view between teaching staff and senior business administration students, by a structured questionnaire, with the aim of checking eventually similarities and/or differences in both groups perception. On one hand the results of this study have revealed similarities in the teaching staff and students perception, which have strongly occurred considering the teaching staff competences and the teaching strategies. On the other hand, the competences development in the specific formation has shown differences between the teachers and the students points of view